Effectiveness of continuous glucose monitoring in patient management of Type 2 Diabetes Mellitus: an umbrella review of systematic reviews from 2011 to 2024 - Yong Yi Tan; Enhui Suan; Gerald Choon Huat Koh; Suhana Binte Suhairi; Shilpa Tyagi (Archives of Public Health)
Abstract Background Continuous glucose monitoring (CGM) is increasingly popular for managing Type 2 Diabetes Mellitus (T2DM). Many systematic reviews have reported on CGM's effectiveness, but with heterogeneous methodologies and objectives. We aim to conduct an umbrella review (UR) to consolidate a most contemporaneous and comprehensive evidence base comparing CGM with self-monitoring of blood glucose or usual care (SMBG/UC). Methods Ovid MEDLINE, Ovid Embase, Cochrane Database of Systematic Reviews, CINAHL, Epistemonikos, SCOPUS, Web of Science and PubMed were searched from their dates of inception to 28th June 2024. Systematic reviews (SR) with or without meta-analyses comparing the use of CGM with SMBG or usual care (UC) for T2DM management in patients treated with or without insulin were included. Narrative synthesis of HbA1c, glycemic variability metrics and other physical measurements were done. Corrected covered area (CCA) was calculated to assess suitability of meta-meta-analysis. Results 31 SRs were included in this UR. There was high overlap within meta-analyses of HbA1c, time-in-range (TIR), time-above-range (TAR) and time-below-range (TBR). A primary study-level meta-analysis demonstrated that compared to SMBG/UC, CGM was associated with significantly greater HbA1c decrease (n = 11,494, MD = -0.40% [95% CI: -0.54 to -0.25]), TIR increase (n = 1452, MD = 6.00% [95%CI: 3.13 to 8.88]) and TAR decrease (n = 1113, MD = -4.33% [95%CI: -8.37 to -0.28]).These findings were invariant with CGM modality, study funding, pre-existing insulin treatment and risk-of-bias. Meta-analysis of patient reported outcome measures (PROMs) demonstrated insignificant differences in PROMs with CGM use compared to SMBG/UC. Conclusion CGM could lead to better clinical outcomes than SMBG/UC and was of moderate evidence certainty (GRADE), while its effect on PROMs remains inconclusive. We recommend the introduction of CGM into standard care alongside SMBG for T2DM and further research exploring patient experience and acceptability of CGM use.